2021
DOI: 10.21608/aeji.2021.81275.1151
|View full text |Cite
|
Sign up to set email alerts
|

Role of Serum Ascites Albumin Gradient (SAAG) and Portal Vein Congestion Index as Non-‎Invasive Methods for Prediction of Esophageal Varices in Cirrhotic Patients ‎

Abstract: Background and aim: Majority of cirrhotic patients develop varices, the rate of variceal bleeding is 10-30% yearly with death rate from bleeding is 17-57%. esophagogastroduodenoscopy (EGD) is an invasive and unpleasant technique carrying rare but serious complications. We aimed to investigate the serum ascites albumin gradient (SAAG) and portal vein congestion index (PCI) as non-invasive methods for prediction of esophageal varices (EV) in patients with liver cirrhosis. Patients and Methods: 125 cirrhotic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that when liver cirrhosis is found, patients should be checked for the presence of EV. However, endoscopy is an invasive and unpleasant procedure that can have uncommon but serious side effects [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that when liver cirrhosis is found, patients should be checked for the presence of EV. However, endoscopy is an invasive and unpleasant procedure that can have uncommon but serious side effects [4].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have tried to determine whether the existence esophageal varices may be detected by non-invasive measures, eliminating the requirement for screening endoscopy in all cirrhotic patients [3]. However, there is no universal consensus on the optimum variable for predicting EV risk [4]. In the absence of any other known causes of cardiac illness, cirrhotic patients frequently develop cirrhotic cardiomyopathy, a kind of chronic heart disease characterized by altered diastolic relaxation and/or impaired contractile response to stress [5].…”
Section: Accordingmentioning
confidence: 99%